Pembuatan dan Karakterisasi Benang Polipropilena (PP) Side by Side Dengan Menggunakan Mesin Pemintalan Leleh - Indrianti, Efie; Manalu, Robinson; Prianto, Juan; Martiningsih (Sekolah Tinggi Teknologi Wastukancana, 2025)
The research develops a synthetic yarn with combination of 2 polymers (bicomponent) to produce a bicomponent yarn with certain characteristics. The bicomponent polypropylene yarn side by side was successfully carry out in this research and the result were analyzed. The yarn tensile strength is 3.80 g/denier, the elongation is 78.89 %, and the yarn number is 72 denier, according to the results of the analysis. The morphology of the longitudinal and transverse bicomponent yarns was examined under a microscope, revealing the bicomponent yarn's side-by-side structure, which created two colored yarns, black and white.